KEANEKARAGAMAN MOLEKULER ISOLAT Pleurotus spp. TIPE LIAR DAN DOMESTIK SERTA KUALITAS PRODUKSINYA - Noverita Noverita (VIS VITALIS Jurnal Ilmiah Biologi, 2008)
Oyster mushroom (Plerotus spp.) are edible mushrooms with high diversity. Cultivated oyster mushroom isolates in Indonesia are from local isolates as well as from outside Indonesia. Report on their genetic diversity are still scarce especially on their molecular aspects. This study was aimed to identify genetic diversity and product qualities of several local and domestic isolates. Molecular analysis onPlerotus spp. isolates were done by using RAPD molecular marker with five primers (RP-2, RP-3 RP- 3, RP-4 and RP-6), and qualities product were observed based on number and length stem, cap diameter, wet weight of frutting body and biological eficience.The results indicated that isolates HHB 327, Sp 1, Sp 2, Sp 3, Sp 4 and Sp 5 (white color Pleurotus ) can be considered as one group with perfect (100%) similarity index. These six isolates group with isolate HHB 307 (the color not determined) had similarity index of 81,9%. The similar results were shown by HHB 215 and Sp 6 (brown color Pleurotus) isolates which both can be considered as one group with perfect similarity index. This latter group form larger group with HHB 328 (brown color Pleurotus) at 90 % similarity index, and this group with isolate HHB 247 (pink color Pleurotus ) had a similarity index of 81,9%. Isolate HHB 247 showed highest product qualities.